Investigation of Vascular Endothelial Growth Factor Polymorphisms on Risk, Metastasis, Laterality, and Prognosis of Colorectal Cancer in Turkish Subjects - SÜSLEYİCİ, BELGİN (My University, 2022)
Objectives: Tumor angiogenesis is known to support the spread and invasion of tumor cells, allow distant organ metastasis, resulting in worse prognosis and mortality. Since vascular endothelial growth factor-A (VEGF-A) is the major regulator of angiogenesis, in the present study, the associations of VEGF-A +405G>C and -460C>T polymorphisms with risk, primary tumor location, prognosis, and metastasis of colorectal cancer (CRC) were investigated in Turkish subjects.Material and Methods: A total of 153 subjects consisting of 74 controls and 79 CRC diagnosed patients were included in the study. VEGF-A +405G>C and -460C>T polymorphisms were analyzed using Agena MassARRAY platform.Results: VEGF +405GC+CC genotypes were found to be significantly associated with left colon cancer (unadjusted odds ratio [OR] = 5.208 confidence interval [95% CI]: 1.064-25.496, p = 0.04). VEGF -460TT and CT+TT genotypes were associated with reduced liver metastasis risk (OR = 0.080 95% CI: 0.009-0.689 p = 0.02 and OR = 0.191 95% CI: 0.039-0.925, p = 0.04, respectively). Patients with VEGF +405GG genotype showed longer progression-free survival as a response to bevacizumab treatment (Log rank = 6.92, p = 0.03).Conclusion: According to our results, VEGF +405G>C and -460C>T polymorphisms were found to be associated with CRC prognosis, sidedness, and metastasis. Our findings should be conducted in further studies.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Tıbbi Genetik; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Medicine; Health Sciences; Internal Medicine Sciences; Medical Genetics; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Moleküler Biyoloji ve Genetik; Yaşam Bilimleri (LIFE); GENETİK VE KALITIM; BIOCHEMISTRY & MOLECULAR BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); GENETICS & HEREDITY; Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Genetik; Klinik Biyokimya; Kanser Araştırmaları; Moleküler Biyoloji; İlaç Keşfi; Yaşlanma; Genel Biyokimya, Genetik ve Moleküler Biyoloji; Biyokimya; Yapısal Biyoloji; Genetik (klinik); Biochemistry, Genetics and Molecular Biology (miscellaneous); Genetics; Clinical Biochemistry; Cancer Research; Molecular Biology; Drug Discovery; Aging; General Biochemistry, Genetics and Molecular Biology; Biochemistry; Structural Biology; Genetics (clinical); VEGF; +405G>C; -460C>T; bevacizumab; colorectal cancer; metastasis; FACTOR GENE POLYMORPHISMS; VEGF GENE; FACTOR EXPRESSION; POTENTIAL TARGET; SUSCEPTIBILITY; ANGIOGENESIS; ASSOCIATION; MECHANISMS; DISEASE; COMMON